Booksmart [videorecording (DVD)] - Dever, Kaitlyn; Feldstein, Beanie; Williams, Jessica, 1989-; Kudrow, Lisa; Forte, Will; Sudeikis, Jason (20th Century Fox Home Entertainment, 2019)
Told from a wildly original, fresh, and modern perspective, this is an unfiltered comedy about high school best friends and the bonds they create that last a lifetime. Capturing the spirit of the times, it is a coming-of-age story for a new generation.